Variation and Acquisition of Spanish Pronouns of Address and Implications for Teaching - Aguilar-Sánchez, Jorge (2018)
Spanish second-person personal pronouns are prescriptively known and recognized in most varieties of Spanish as informal for túand formal for usted(you [sg.] and you [sg.]), including the pedagogical variety taught as a foreign or second language. Although vosexists as a third form in some varieties of Spanish, the present study focuses on the former two because they are the ones present in textbooks of Spanish as a foreign language. The present work studies variation found in the social deixis (i.e., relationships from the egocentric, the self, the perspective of the speaker) and explores the choices second language learners, as well as native speakers of Spanish, make when choosing between these two pronouns. A modified computerized discourse completion test, which makes use of audio, video, and text, was used to elicit participants´ responses to eight scenarios in a more naturalistic way. It included variables that have been shown to affect participants’ choices as well as variables that have not yet been studied such as participants’ personality and clothing. Findings of the present study suggest that linguistic, pragmatic, and/or social variables are not the only ones that influence L2 learners’ and native speakers’ choices about pronouns of address. Results show that psychological variables such as personality and visual cues such as outfit are influential in both L2 learners’ and native speakers’ choices. The aforementioned findings have implications as to how educators approach the teaching of these forms to facilitate their use and acquisition in natural and instruction settings, especially in a learner-centered, proficiency- oriented classroom.